Expression, purification and characterization of the dimeric protruding domain of Macrobrachium rosenbergii nodavirus capsid protein expressed in Escherichia coli - Chong, Li Chuin; Ganesan, Hagilaa; Yong, Chean Yeah; Tan, Wen Siang; Ho, Kok Lian (Public Library of Science, 2019)
Macrobrachium rosenbergii nodavirus (MrNV) is the causative agent of white tail disease (WTD) which seriously impedes the production of the giant freshwater prawn and has a major economic impact. MrNV contains two segmented RNA molecules, which encode the RNA dependent RNA polymerase (RdRp) and the capsid protein (MrNV-CP) containing 371 amino acid residues. MrNV-CP comprises of the Shell (S) and the Protruding (P) domains, ranging from amino acid residues 1–252 and 253–371, respectively. The P-domain assembles into dimeric protruding spikes, and it is believed to be involved in host cell attachment and internalization. In this study, the recombinant P-domain of MrNV-CP was successfully cloned and expressed in Escherichia coli, purified with an immobilized metal affinity chromatography (IMAC) and size exclusion chromatography (SEC) up to ~90% purity. Characterization of the purified recombinant P-domain with SEC revealed that it formed dimers, and dynamic light scattering (DLS) analysis demonstrated that the hydrodynamic diameter of the dimers was ~6 nm. Circular dichroism (CD) analysis showed that the P-domain contained 67.9% of beta-sheets, but without alpha-helical structures. This is in good agreement with the cryo-electron microscopic analysis of MrNV which demonstrated that the P-domain contains only beta-stranded structures. Our findings of this study provide essential information for the production of the P-domain of MrNV-CP that will aid future studies particularly studies that will shed light on anti-viral drug discovery and provide an understanding of virus-host interactions and the viral pathogenicity.